Hysteria complicated by ecstasy : the case of Nanette Leroux - Goldstein, Jan, 1946- (Princeton University Press, 2010)
Hysteria Complicated by Ecstasy offers a rare window into the inner life of a person ordinarily inaccessible to historians: a semiliterate peasant girl who lived almost two centuries ago, in the aftermath of the French Revolution. Eighteen-year-old Nanette Leroux fell ill in 1822 with a variety of incapacitating nervous symptoms. Living near the spa at Aix-les-Bains, she became the charity patient of its medical director, Antoine Despine, who treated her with hydrotherapy and animal magnetism, as hypnosis was then called. Jan Goldstein translates, and provides a substantial introduct.